Cord-blood black carbon particle burden is associated with a C19MC small extracellular vesicle miRNA signature enriched for neurodevelopmental pathways - Houman Kahroba; Kenneth Vanbrabant; Marcel van Herwijnen; Rick Kamps; Matthew Walker; Dagmar Waiblinger; Marcel Ameloot; Michelle Plusquin; John Wright; Tim Nawrot; Theo M. de Kok; Julian Krauskopf (Environmental Research, 2026)

Cord-blood black carbon burden is associated with coordinated inflammatory and heme-metabolic transcriptional programs at birth in Bradford, United Kingdom - Houman Kahroba; Kenneth Vanbrabant; Marcel van Herwijnen; Rick Kamps; Dagmar Waiblinger; Matthew Walker; Marcel Ameloot; Maarten Roeffaers; John Wright; Tim Nawrot; Theo M. de Kok; Julian Krauskopf (Science of The Total Environment, 2026)

Real-time satellite monitoring of the 2024–2025 dyke intrusion sequence at Fentale-Dofen volcanoes, Ethiopia - Lin Way; Juliet Biggs; Weiyu Zheng; Milan Lazecky; Edna W. Dualeh; Tim Wright; Raphaël Grandin; Arthur Hauck; Sue Loughlin; Julia Crummy; Elias Lewi (Bulletin of Volcanology, 2025)

Mid-crustal strain localisation triggered by localised fluid influx and activation of dissolution–precipitation creep - Manon Carpenter; Sandra Piazolo; Tim Craig; Tim J. Wright (Journal of Structural Geology, 2025)

Deformation of the Ecuadorian Inter-Andean valley and surroundings from a combined InSAR-GNSS velocity field 2017–2023. - Pedro Alejandro Espín Bedón; John R. Elliott; Tim J. Wright; Susanna Ebmeier; Patricia Mothes; Milan Lazecky; Yasser Maghsoudi; Jack McGrath; Daniel Andrade (Journal of South American Earth Sciences, 2025)

Imaging viscosity after the 2021 Mw 7.4 Maduo earthquake: Insights on the regional rheology variation beneath the Bayan Har block - Zhen Li; Wei Xiong; Andrew Hooper; Zeyan Zhao; Yuan Gao; John R. Elliott; Tim J. Wright; Han Yue; Teng Wang (Earth and Planetary Science Letters, 2025)

Scientific response to the 2024–2025 dyke intrusions in the Fentale-Dofen Region, Ethiopia: geophysical monitoring, surface manifestations, and hazard mapping - Elias Lewi; Juliet Biggs; Atalay Ayele; Tim Wright; Carolina Pagli; Derek Keir; Yechale Ali; Genet Assefa; Hua Wang; Alessandro La Rosa; Lin Way; Filagot Mengistu; et al. (Bulletin of Volcanology, 2025)
In continental rifts, tectonic deformation, magmatic processes, and earthquakes interact dynamically reflecting the crust’s complex response to extensional stress and evolving subsurface and surface conditions. Recent seismotectonic activity in the Fentale-Dofen region of the Main Ethiopian Rift was driven by the intrusion of several dykes reaching up to ~ 50 km in length observed using satellite radar interferometry. Over 300 earthquakes with magnitude 4 or greater were reported by international seismic networks and the GNSS site at Addis Ababa moved ~ 20 mm to the west. These and other observations on the ground were used to create a highly simplified hazard map and 75,000 people were evacuated. Although no magmatic eruption occurred, the earthquakes triggered landslides and caused infrastructure damage, especially to buildings and roads. Here we provide a preliminary analysis of the patterns of earthquakes, ground deformation, and surface manifestations from 2024 to 2025, with a focus on the underlying mechanisms contributing to seismic sequences in the area and key unresolved scientific questions. We discuss how scientific evidence was used to inform decision-makers and examine the short- and long-term implications for critical infrastructure and nearby communities. Finally, we emphasize the importance of real-time monitoring, proactive risk management, and the need for continuous observation and improved early warning systems to reduce future seismic and volcanic risks.

Bridging knowledge gaps in human chemical exposure via drinking water with non-target screening - Davide Ciccarelli; Saer Samanipour; Helena Rapp-Wright; Stefan Bieber; Thomas Letzel; Jake W. O’Brien; Tim Marczylo; Timothy W. Gant; Paolo Vineis; Leon P. Barron (Critical Reviews in Environmental Science and Technology, 2025)

Co-eruptive, endogenous edifice growth, uplift during 4 years of eruption at Sangay Volcano, Ecuador - Pedro Alejandro Espín Bedón; Susanna K. Ebmeier; John R. Elliott; Tim J. Wright; Patricia Mothes; Valérie Cayol; Yasser Maghsoudi; Milan Lazecký; Daniel Andrade (Journal of Volcanology and Geothermal Research, 2024)

Deciphering interseismic strain accumulation and its termination on the central-eastern Altyn Tagh fault from high-resolution velocity fields - Dehua Wang; John R. Elliott; Gang Zheng; Tim J. Wright; Andrew R. Watson; Jack D. McGrath (Earth and Planetary Science Letters, 2024)

Early life exposure to mercury and relationships with telomere length and mitochondrial DNA content in European children - Manuel Lozano; Rosemary R.C. McEachan; John Wright; Tiffany C. Yang; Courtney Dow; Manik Kadawathagedara; Johanna Lepeule; Mariona Bustamante; Lea Maitre; Martine Vrijheid; Anne Lise Brantsæter; Helle Margrete Meltzer; et al. (Science of The Total Environment, 2024)

Tectono-sedimentary evolution of the Suriname margin in the cretaceous: A sequence-stratigraphic framework - V. Delhaye-Prat; Julien Bourget; Gwladys Gaillot; Jérémie Gaillot; François Sapin; Charlotte Fillon; Jing Ye; Tim Wright; Anne-Claire Chaboureau; Nicoletta Buratti; Benoit Magnier; Andrei Belopolsky; et al. (Earth-Science Reviews, 2024)

Microplastic pollution on historic facades: Hidden ‘sink' or urban threat? - Katrin Wilhelm; Sam Woor; Michelle Jackson; Dania Albini; Neil Young; Phani Karamched; Miriam C. Policarpo Wright; Josep Grau-Bove; Scott Allan Orr; Jack Longman; Tim de Kock (Environmental Pollution, 2024)

Accelerating ocean species discovery and laying the foundations for the future of marine biodiversity research and monitoring - Alex David Rogers; Hannah Appiah-Madson; Jeff A. Ardron; Nicholas J. Bax; Punyasloke Bhadury; Angelika Brandt; Pier-Luigi Buttigieg; Olivier De Clerck; Claudia Delgado; Daniel L. Distel; Adrian Glover; Judith Gobin; et al. (Frontiers in Marine Science, 2023)
Ocean Census is a new Large-Scale Strategic Science Mission aimed at accelerating the discovery and description of marine species. This mission addresses the knowledge gap of the diversity and distribution of marine life whereby of an estimated 1 million to 2 million species of marine life between 75% to 90% remain undescribed to date. Without improved knowledge of marine biodiversity, tackling the decline and eventual extinction of many marine species will not be possible. The marine biota has evolved over 4 billion years and includes many branches of the tree of life that do not exist on land or in freshwater. Understanding what is in the ocean and where it lives is fundamental science, which is required to understand how the ocean works, the direct and indirect benefits it provides to society and how human impacts can be reduced and managed to ensure marine ecosystems remain healthy. We describe a strategy to accelerate the rate of ocean species discovery by: 1) employing consistent standards for digitisation of species data to broaden access to biodiversity knowledge and enabling cybertaxonomy; 2) establishing new working practices and adopting advanced technologies to accelerate taxonomy; 3) building the capacity of stakeholders to undertake taxonomic and biodiversity research and capacity development, especially targeted at low- and middle-income countries (LMICs) so they can better assess and manage life in their waters and contribute to global biodiversity knowledge; and 4) increasing observational coverage on dedicated expeditions. Ocean Census, is conceived as a global open network of scientists anchored by Biodiversity Centres in developed countries and LMICs. Through a collaborative approach, including co-production of science with LMICs, and by working with funding partners, Ocean Census will focus and grow current efforts to discover ocean life globally, and permanently transform our ability to document, describe and safeguard marine species.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mapping Seafloor Relative Reflectance and Assessing Coral Reef Morphology with EAARL-B Topobathymetric Lidar Waveforms - Nicholas Wilson; Christopher E. Parrish; Tim Battista; C. Wayne Wright; Bryan Costa; Richard K. Slocum; Jennifer A. Dijkstra; Matthew T. Tyler (Estuaries and Coasts, 2022)
Topobathymetric lidar is becoming an increasingly valuable tool for benthic habitat mapping, enabling safe, efficient data acquisition over coral reefs and other fragile ecosystems. In 2014, a novel topobathymetric lidar system, the Experimental Advanced Airborne Research Lidar-B (EAARL-B), was used to acquire data in priority habitat areas in the U.S. Virgin Islands (USVI), spanning the 0–44-m depth range. In this study, new algorithms and procedures were developed for generating seafloor relative reflectance, along with a suite of shape-based waveform features from EAARL-B. Waveform features were then correlated with percent cover of coral morphologies, domed and branched, and total cover of hard and soft corals. Results show that the EAARL-B can be used to produce useful seafloor relative reflectance mosaics and also that the additional waveform shape-based features contain additional information that may benefit habitat classification—specifically, to aid in distinguishing among hard corals and their coral morphologies, domed and branched. Knowing the spatial extent of changes in coral communities is important to the understanding of resiliency of coral reefs under stress from human impacts.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

How to quantify thermal acclimation capacity? - Sigurd Einum; Irja Ratikainen; Jonathan Wright; Christophe Pélabon; Claus Bech; Fredrik Jutfelt; Clare Stawski; Tim Burton (Global Change Biology, 2019)

Running off the road: roadside non-native plants invading mountain vegetation - Keith L. McDougall; Jonas Lembrechts; Lisa J. Rew; Sylvia Haider; Lohengrin A. Cavieres; Christoph Kueffer; Ann Milbau; Bridgett J. Naylor; Martin A. Nuñez; Anibal Pauchard; Tim Seipel; Karina L. Speziale; et al. (Biological Invasions, 2018)

Repeated sublethal freshwater exposures reduce the amoebic gill disease parasite, Neoparamoeba perurans , on Atlantic salmon - Daniel William Wright; Barbara Nowak; Frode Oppedal; Phil Crosbie; Lars Helge Stien; Tim Dempster (Journal of Fish Diseases, 2018)
Freshwater bathing is one of the main treatment options available against amoebic gill disease ( AGD ) affecting multiple fish hosts in mariculture systems. Prevailing freshwater treatments are designed to be long enough to kill Neoparamoeba perurans , the ectoparasite causing AGD , which may select for freshwater tolerance. Here, we tested whether using shorter, sublethal freshwater treatment durations are a viable alternative to lethal ones for N. perurans (2–4 hr). Under in vitro conditions, gill‐isolated N. perurans attached to plastic substrate in sea water lifted off after ≥2 min in freshwater, but survival was not impacted until 60 min. In an in vivo experiment, AGD ‐affected Atlantic salmon Salmo salar subjected daily to 30 min (sublethal to N. perurans ) and 120 min (lethal to N. perurans ) freshwater treatments for 6 days consistently reduced N. perurans cell numbers on gills (based on qPCR analysis) compared to daily 3 min freshwater or seawater treatments for 6 days. Our results suggest that targeting cell detachment rather than cell death with repeated freshwater treatments of shorter duration than typical baths could be used in AGD management. However, the consequences of modifying the intensity of freshwater treatment regimes on freshwater tolerance evolution in N. perurans populations require careful consideration.

First recorded eruption of Nabro volcano, Eritrea, 2011 - Berhe Goitom; Clive Oppenheimer; James O. S. Hammond; Raphaël Grandin; Talfan Barnie; Amy Donovan; Ghebrebrhan Ogubazghi; Ermias Yohannes; Goitom Kibrom; J- Michael Kendall; Simon A. Carn; David Fee; et al. (Bulletin of Volcanology, 2015)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

The Krafla fissure swarm, Iceland, and its formation by rifting events - Ásta Rut Hjartardóttir; Páll Einarsson; Emma Bramham; Tim J. Wright (Bulletin of Volcanology, 2012)

Population structure of Cylindrocladium parasiticum infecting peanuts (Arachis hypogaea) in Georgia, USA - Louwrance P. Wright; Andrew J. Davis; Brenda D. Wingfield; Pedro W. Crous; Tim Brenneman; Michael J. Wingfield (European Journal of Plant Pathology, 2010)

Radar interferometry time series analysis of Mashhad subsidence - Maryam Dehghani; Mohammad Javad Valadan Zoej; Sassan Saatchi; Juliet Biggs; Barry Parsons; Tim Wright (Journal of the Indian Society of Remote Sensing, 2009)

[Cover]Massive dyke intrusion detected by satellite radar interferometry, Afar Rift, Ethiopia - Tim Wright (International Journal of Remote Sensing, 2008)

Rapid pregermination and germination responses of Erysiphe pisi conidia to contact and light - Keiko Fujita; Alison J. Wright; Akane Meguro; Hitoshi Kunoh; Tim L.W. Carver (Journal of General Plant Pathology, 2004)

A Dynamic Life‐Cycle Energy Model of Mobile Phone Take‐back and Recycling - Jake McLaren; Lucy Wright; Stuart Parkinson; Tim Jackson (Journal of Industrial Ecology, 1999)
Summary This paper reports the results of a life‐cycle energy model of a pilot mobile phone “take‐back” scheme carried out by the Cellular Phones Take‐back Working Group of the European Trade Organisation for the Telecommunication and Professional Electronics Industry (ECTEL) in the United Kingdom (UK) and Sweden during 1997. Using data collected from the scheme, the model calculates a snapshot “energy balance” associated with mobile phone take‐back for a variety of phone types and take‐back scenarios in the year 1997. It also develops a time‐series model for the UK, describing the environmental implications of different take‐back scenarios in the future. Because of its emphasis on interactive, dynamic modeling techniques, the methodology developed for the life‐cycle model has the potential for wide application in regulatory and industrial decision making.